2018
DOI: 10.1007/s00345-018-2281-z
|View full text |Cite
|
Sign up to set email alerts
|

Pair-matched patient-reported quality of life and early oncological control following focal irreversible electroporation versus robot-assisted radical prostatectomy

Abstract: PurposeThe design, conduct and completion of randomized trials for curative prostate cancer (PCa) treatments are challenging. To evaluate the effect of robot-assisted radical prostatectomy (RARP) versus focal irreversible electroporation (IRE) on patient-reported quality of life (QoL) and early oncological control using propensity-scored matching.MethodsPatients with T1c–cT2b significant PCa (high-volume ISUP 1 or any 2/3) who received unifocal IRE were pair-matched to patients who received nerve-sparing RARP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Another group reported on a propensity matched comparison of 50 patients undergoing another type of ablation called irreversible electroporation to 50 radical prostatectomy patients but with only 12 months follow-up. Again, functional outcomes were superior with focal therapy, but failure was significantly higher with 4 patients undergoing salvage therapy whilst none in the radical prostatectomy group experienced biochemical failure at 12months (16). Although not a directly comparable study, Tay et al assessed outcomes from wholegland cryotherapy to focal cryotherapy and showed that using the Phoenix definition for biochemical failure there was no statistically significant difference in the 5-year biochemical disease-free survival rates (76.4% whole-gland vs. 70.0% focal, p=0.26) (17).…”
Section: Discussionmentioning
confidence: 95%
“…Another group reported on a propensity matched comparison of 50 patients undergoing another type of ablation called irreversible electroporation to 50 radical prostatectomy patients but with only 12 months follow-up. Again, functional outcomes were superior with focal therapy, but failure was significantly higher with 4 patients undergoing salvage therapy whilst none in the radical prostatectomy group experienced biochemical failure at 12months (16). Although not a directly comparable study, Tay et al assessed outcomes from wholegland cryotherapy to focal cryotherapy and showed that using the Phoenix definition for biochemical failure there was no statistically significant difference in the 5-year biochemical disease-free survival rates (76.4% whole-gland vs. 70.0% focal, p=0.26) (17).…”
Section: Discussionmentioning
confidence: 95%
“…A possible advantage using DCE images may be gained in the assessment of the primary tumor. As the landscape of local therapy for prostate cancer is evolving, and concepts of individualized therapy, such as focal therapy (FT) [ 22 , 23 ], broader application of active surveillance (AS) [ 24 , 25 ], and image-guided radiation, are becoming more prevalent, the need for accurate imaging is also increasing. In these settings, better visibility and improved estimation of tumor location and size are key factors to success.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive techniques are used for organ-confined PCa and are a novel strategy for targeted treatment, while preserving healthy tissue and subsequently reduce treatment-related morbidity [4]. Currently, a wide variety of energy sources seem to be capable for FT, i.e., focal laser ablation (FLA) cryosurgery, high intensity-focused ultrasound (HIFU), radiofrequency, microwave, and irreversible electroporation/nanoknife (IRE) [57].…”
Section: Introductionmentioning
confidence: 99%